Keterbukaan Perdagangan di 6 Negara ASEAN : Peran Foreign Direct Investment, Pengeluaran Pemerintah, dan Inflasi - Wayan Dea Maharani Ardiana; Anak Agung Bagus Putu Widanta (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
Trade openness is one of the key indicators reflecting a country’s integration into the global economy. During the period 1995 – 2023, the level of the trade openness in six ASEAN countries (Singapore, Brunei Darussalam, Indonesia, Thailand, Cambodia, and Philippines) showed varying patterns. In addition, external factors such as inflows of foreign direct investment (FDI), government expenditure, and inflation are expected to influence trade openness in these countries. This study aims to analyze the effect of influence foreign direct investment, government expenditure, and inflation on trade openness in 6 Countries ASEAN. The variables used in this study include trade openness as the dependent variable, and foreign direct investment, government expenditure, and inflation as the independent variables. The analytical method applied is panel data regression with a quantitative approach, using secondary data obtained from the World Bank. The results show that simultaneously foreign direct investment, government expenditure, and inflation have a significant effect on trade openness. Partially, foreign direct investment and government expenditure have a positive and significant effect, while inflation has a negative and significant effect. The conclusions of this study is that trade openness in 6 Countries ASEAN is strongly influenced by foreign capital inflows and the effectiveness of government expenditure, but it is vulnerable to decline when price instability occurs.